2012
DOI: 10.1603/en11109
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance, Number of Annual Generations, and Effect of an Entomopathogenic Fungus on Phlebotomus papatasi (Diptera: Psychodidae)

Abstract: The monthly density of the sand fly, Phlebotomus Papatasi Scopoli (Diptera: Psychodidae), was monitored during 2009 at Burg El-Arab, a rural district located close to the Mediterranean coast of Egypt. The number of annual generations and the efficacy of microbial control by the entomopathogenic fungus, Metrahizium anisopliae (Metsch.) Sorok (Ma79), were determined in the laboratory under atmospheric conditions, simulating those of the animal shelters in the study area. We used two collecting techniques; CDC l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Previous studies have investigated the effects of environmental variables on the occurrence of leishmaniasis [19,35,36,37,38,39,40,41]. Several authors have previously used times series analyses to study infectious disease incidences [13,42,43,44,45,46,47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have investigated the effects of environmental variables on the occurrence of leishmaniasis [19,35,36,37,38,39,40,41]. Several authors have previously used times series analyses to study infectious disease incidences [13,42,43,44,45,46,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Gálvez et al [39] reported that the seasonal abundance of P. perniciosus sandflies in Central Spain had two peaks in July and September, while it reported a single peak of P. ariasi in August. El-Shazly et al [40] reported peaks of P. perniciosus in July and October in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of temperature is key to the survival and lifespan of sand flies [51]. Low temperatures negatively affects their longevity [50] as well as high temperatures [51].…”
Section: Discussionmentioning
confidence: 99%
“…Shoukry and Morsy (20110 in a preliminary survey in Toshka District reported Psammomyes obesus Cretzchmar, 1828 the main reservoir of ZCL and Phlebotomus papatasii (Scopoli), but did not found human cases of ZCL. El-Shazly et al (2012) found that the monthly density of the sand fly, P. papatasi was monitored during 2009 at Burg El-Arab, a rural district located close to the Mediterranean coast of Egypt. The annual generations and the efficacy of microbial control by the entomopathogenic fungus, Metrahizium anisopliae were determined in the laboratory under atmospheric conditions, simulating those of the animal shelters in the study area.…”
Section: Review and Discussionmentioning
confidence: 99%